2009
DOI: 10.1088/0256-307x/26/7/077106
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Band Calculations on Electronic Structures of Ag-Doped Rutile and Anatase TiO2

Abstract: The electronic structures of Ag-doped rutile and anatase TiO2 are studied by first-principles band calculations based on density functional theory with the full-potential linearized-augmented-plane-wave method. New occupied bands are found between the band gaps of both Ag-doped rutile and anatase TiO2. The formation of these new bands can be explained mainly by their orbitals of Ag 4d states mixed with Ti 3d states and are supposed to contribute to their visible light absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 18 publications
6
8
0
Order By: Relevance
“…From the results of PDOS of Ag and Au atoms in Fig.3 (b), the d electronic states are mainly attributed to the Ag and Au, while the p electronic states are due to the O 2p states. These results are consistent with the previous experimental and theoretical results [5,6,10,36]. In early calculations, the Ag-doped TiO 2 with high concentration (6.25 %) in 48 atoms system also produced middle states, and it was 0.65 eV above the valence band and 0.76 eV below the conduction band [5].…”
Section: Calculation Methodssupporting
confidence: 91%
See 1 more Smart Citation
“…From the results of PDOS of Ag and Au atoms in Fig.3 (b), the d electronic states are mainly attributed to the Ag and Au, while the p electronic states are due to the O 2p states. These results are consistent with the previous experimental and theoretical results [5,6,10,36]. In early calculations, the Ag-doped TiO 2 with high concentration (6.25 %) in 48 atoms system also produced middle states, and it was 0.65 eV above the valence band and 0.76 eV below the conduction band [5].…”
Section: Calculation Methodssupporting
confidence: 91%
“…The first principles calculations of electronic structures of the Ag-doped anatase TiO 2 were carried out, and the researchers supposed that the visible light absorption was due to the Ag 4d states mixed with Ti 3d states in the band gap. In addition, Ag was doped and deposited on TiO 2 simultaneously by experiment, which was more effective than the single deposition, because Ag and Ag + could both act as electron traps to enhance photocatalytic activity [5][6][7]. The results of Liu et al showed the enhanced photocatalytic activity of Ag-doped TiO 2 particles, because the structure modification of TiO 2 resulted by Ag doping could facilitate the produce of O vacancy [8].…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al [21] reported that the density functional theory (DFT) calculation further confirmed the red shift of absorption edges and the narrowing of the band gap of Fe-TiO 2 nanorods. Hou et al [22] showed that new occupied bands were found in the band gap of Ag-doped anatase TiO 2 . The formation of these new bands results from the hybridization of Ag 4 d and Ti 3 d states, and they were supposed to contribute to visible light absorption.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, modifications of TiO 2 with zirconia, silver, and gold were reported to improve its photocatalytic properties. Noble metals are thought to aid charge transfer at the semiconductor‐metal interface via formation of a Schottky barrier , to hinder recombination processes by acting as charge traps , to enhance absorption of light due to the surface plasmon resonance (Ag , Au ) and presence of Ag‐ or Au‐induced gap states (TiO 2 /Ag and TiO 2 /Au ). Both UV and visible PC reactions were tested on noble metal‐doped TiO 2 .…”
Section: Introductionmentioning
confidence: 99%